Residential selection across the life course: adolescent contextual and individual determinants of neighborhood disadvantage in mid-adulthood. - Per E Gustafsson (Public Library of Science (PLoS), 2013)
Background Numerous cross-sectional studies have examined neighborhood effects on health. Residential selection in adulthood has been stressed as an important cause of selection bias but has received little empirical attention, particularly its determinants from the earlier life course. The present study aims to examine whether neighborhood, family, school, health behaviors and health in adolescence are related to socioeconomic disadvantage of one's neighborhood of residence in adulthood. Methods Based on the prospective Northern Swedish Cohort (analytical N = 971, 90.6% retention rate), information was collected at age 16 years concerning family circumstances, school adjustment, health behaviors and mental and physical health. Neighborhood register data was linked to the cohort and used to operationalize aggregated measures of neighborhood disadvantage (ND) at age 16 and 42. Data was analyzed with linear mixed models, with ND in adulthood regressed on adolescent predictors and neighborhood of residence in adolescence as the level-2 unit. Results Neighborhood disadvantage in adulthood was clustered by neighborhood of residence in adolescence (ICC = 8.6%). The clustering was completely explained by ND in adolescence. Of the adolescent predictors, ND (b = .14 (95% credible interval = .07-.22)), final school marks (b = -.18 (-.26--.10)), socioeconomic disadvantage (b = .07 (.01-.14)), and, with borderline significance, school peer problems (b = .07 (-.00-.13)), were independently related to adulthood ND in the final adjusted model. In sex-stratified analyses, the most important predictors were school marks (b = -.21 (-.32--.09)) in women, and neighborhood of residence (ICC = 15.5%) and ND (b = .20 (.09-.31)) in men. Conclusions These findings show that factors from adolescence - which also may impact on adult health - could influence the neighborhood context in which one will live in adulthood. This indicates that residential selection bias in neighborhood effects on health research may have its sources in early life.